2013
DOI: 10.4238/2013.december.19.16
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of coffee seed oxidation and germination processes during drying

Abstract: ABSTRACT. Coffee (Coffea arabica L.) seeds are sensitive to desiccation and oxidative stress during drying processes. We investigated the effect of drying and moisture levels on germinationrelated gene expressions associated with enzymatic systems that prevent oxidative stress in coffee seeds. Coffee seeds collected at physiological maturity were subjected to slow and quick drying to 40, 30, 20, and 12% moisture levels (wet basis), and as the control, seeds without drying were used. The seeds' physiological qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…Therefore, it would be plausible that the peak observed on HpCAT1 expression might have occurred earlier during the first stages of H. perforatum seeds germination (before 4 dps), when HpCAT1 is more required, and that the subsequent decrease on transcript accumulation that we observed might be related to the necessity of maintaining ROS at adequate levels for cellular survival. Indeed, it has been reported that excessive removal of hydrogen peroxide free radicals might reduce the inhibition of the cellular cycle, which is important for DNA repair (Santos et al, 2013 ). In the same line, cellular biology studies have clearly described the beneficial functions of hydrogen peroxide to the cell, beyond causing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it would be plausible that the peak observed on HpCAT1 expression might have occurred earlier during the first stages of H. perforatum seeds germination (before 4 dps), when HpCAT1 is more required, and that the subsequent decrease on transcript accumulation that we observed might be related to the necessity of maintaining ROS at adequate levels for cellular survival. Indeed, it has been reported that excessive removal of hydrogen peroxide free radicals might reduce the inhibition of the cellular cycle, which is important for DNA repair (Santos et al, 2013 ). In the same line, cellular biology studies have clearly described the beneficial functions of hydrogen peroxide to the cell, beyond causing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, cellular biology studies have clearly described the beneficial functions of hydrogen peroxide to the cell, beyond causing oxidative stress. One of these beneficial functions is stopping the cellular cycle during DNA repair after certain types of stress and aging (Santos et al, 2013 ). Accordingly to our results, Mhamdi et al ( 2012 ) reported that a transcriptional down-regulation of CAT could be important to induce or sustain increased H 2 O 2 availability necessary for certain environmental responses or developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…Perkecambahan benih kopi yang lambat dan tidak seragam menjadi kendala dalam pengujian benih kopi yaitu waktu pengujian yang sangat lama. Benih kopi memerlukan waktu berkecambah sekitar 30-45 hari (Brasil 2009;Santos, von Pinho and Rosa 2013;Huang et al 2014) bahkan Kepmentan No. 88 tahun 2017 tentang Pedoman Produksi, Sertifikasi, Peredaran dan Pengawasan Benih Tanaman Kopi memberikan batasan waktu pengujian selama 60 hari.…”
Section: Pendahuluanunclassified
“…The production conditions and the postharvest treatments of coffee beans are responsible for causing modifications in their chemical composition; relevant studies were performed with the aim of determining the effect of the genotype, of the environmental conditions of production, of the forms of processing and of drying the coffee beans, and of their storage on beverage quality (Saath et al, 2014;Isquierdo;Taveira, 2014;Cheng et al, 2016;Ribeiro et al, 2016;Borém et al, 2019) and on the physiological quality of the seed (Rosa et al, 2011;Taveira et al, 2012;Santos;Von Pinho;Rosa, 2013). It is a common consensus among researchers that both the sensory quality of the beverage and the physiological quality of the coffee seed are closely related to the chemical composition of the coffee bean and of the coffee seed, respectively.…”
Section: Lotmentioning
confidence: 99%